Cryptanalysis of a novel image encryption scheme based on improved hyperchaotic sequences - Ozkaynak, Fatih; Ozer, Ahmet Bedri; Yavuz, Sirma (Elsevier Science Bv, 2012)
Chaotic cryptography is a new field that has seen a significant amount of research activity during the last 20 years. Despite the many proposals that use various methods in the design of encryption algorithms, there is a definite need for a mathematically rigorous cryptanalysis of these designs. In this study, we analyze the security weaknesses of the C. Zhu, A novel image encryption scheme based on improved hyperchaotic sequences, Optics Communications 285 (2012) 29-37. By applying chosen plaintext attacks, we show that all the secret parameters can be revealed. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Chaos based cryptography; Cryptanalysis; Chosen-plaintext attack